In-situ pillared MXene as a viable zinc-ion hybrid capacitor. (1st May 2020) - Maughan, Philip A.; Tapia-Ruiz, Nuria; Bimbo, Nuno
Abstract: MXenes are recently discovered two-dimensional materials which have shown great promise in electrochemical energy storage. However, the majority of research has been on lithium and sodium systems, with little work done on multivalent ion systems, which have an urgent need for new electrode materials. In particular, zinc-ion aqueous systems have significant promise due to the widespread use of zinc batteries and the abundance (24th most abundant element on Earth), high specific capacity (>800 mAh g −1 ) and low toxicity of zinc. Only a few materials are reported to act as reversible zinc-ion hosts, hindering developments of this technology. In this work, we demonstrate for the first time that Ti3 C2, the most studied MXene to date, can act as a reversible zinc-ion host for a hybrid capacitor using an aqueous zinc sulphate electrolyte. In addition, we report a novel in-situ pillaring method where CTAB is used to increase the Zn-ion uptake, with capacities up to 189 mAh g −1 . A detailed mechanistic study that encompasses diffraction, microscopy and spectroscopy techniques was conducted to shed light on the structure and kinetics of the system. This understanding was used to optimise the electrode performance, resulting in outstanding cycling stability of over 96% over 1000 cycles. We believe this study will pave the pathway towards designing new pillared MXenes in low-cost Zn-ion aqueous systems.